Tuning of Photoluminescence of Graphene Oxide Based Nanomaterials in the UV‐Visible Region: Formation of Aggregates by H‐Bonding through Water Molecules. Issue 45 (1st December 2022) - Pyne, Dinesh Kumar; Chatterjee, Shovon; Pramanik, Soumalya; Saha, Prosenjit; Biswas, Tuyan; Bali, Somnath; Dutta, Partha; Halder, Arnab
Abstract: To investigate the interaction among the graphene oxide layers by involving surface functional groups, photoluminescence (PL) from graphene oxide (GO), and hydroxyl enriched graphene oxide (OH‐GO) in the UV‐visible region are studied. Tuning of PL is observed by varying the concentration of aqueous dispersion of OH‐GO, obtained by strong alkaline treatment on graphene oxide (GO). FTIR, Raman, XRD, and the microscopic study suggests the structural orderness of the OH‐GO compared to GO. Hydroxyl functional groups at the surface of OH‐GO facilitate the formation of aggregates through hydrogen bonds by involving solvent water molecules and the PL band in the visible region may be originated from such aggregates. With the increase in the concentration of OH‐GO in the aqueous medium, the contribution of the visible PL band is markedly increased along with the decrease in the PL band in the UV region. The time‐resolved study indicates the possibility of energy transfer from the species emitting in the UV region to the species emitting in the visible region. This energy transfer may be responsible for the marked enhancement of the visible band of the PL spectra of OH‐GO at high concentrations. Abstract : Formation of aggregates of GO and hydroxyl enriched graphene oxide (OH ‐ GO) at high concentration due to the interaction among the surface hydroxyl groups of GO sheets through hydrogen bonds by involving solvent water molecules results enhanced photoluminescence (PL) band in the visible region along with UV emission. Such aggregates are characterized as comparatively ordered structure. Energy transfer from the species emitting in the UV region to the aggregates of OH‐GO may be responsible for the PL enhancement in the visible region.